EDUCATION AND ACCESS TO THE INTERNET AMONG FEMALE PENAN YOUTH IN SARAWAK - Juna, Liau; Adam Andani, Mohammed (Borneo Research Council, Inc, 2024)
Access to Information and Communication Technology infrastructure such as the internet is synonymous with access to education which is an essential determinant of future success for individuals and nations. Indicatively, internet is important for both rural and urban communities, especially students. However, there is lack of good internet access in many rural Borneo communities. This study focuses on female students of a Penan secondary school located in the Baram District in the Miri Division of Sarawak. Fieldwork was conducted in the secondary school and nearby bazaars (pasen) to gain firsthand information about educational activities and progression. The article explores the nature of access to internet and how it affects the ability of students to participate effectively in online learning. The article also discusses the academic achievements of the respondents. The research employed a mixed method approach which firstly involved procuring demographic information from a total of 113 female students of the secondary school. This was followed by a survey questionnaire, interviews and field observations. Data from the interviews and observations on the access to internet were analysed thematically. It is revealed that access to education cannot be separated from access to efficient internet connection. Invariably, the educational experience of urban students is different from that of rural communities due to lack of good internet access. The study also reveals that access to internet is constrained by students’ financial ability to own a computer.